L-Value and Energy Dependence of 0.1–50 keV O +, He +, and H + Ions for CME and CIR Storms Over the Entire Van Allen Probes Era - Pandya, Megha; Veenadhari, B.; Ebihara, Yusuke; Reeves, G. D. (My University, 2022)
Our studies report the first observation of L-value and energy sorted correlation of differential fluxes of 0.1–50 keV O +, He +, and H + ions with different geophysical parameters for 29 Coronal Mass Ejected (CME) and 40 Corotating Interaction Region (CIR)-driven geomagnetic storms during the entire Van Allen Probes era. For both solar wind drivers, ions with ≥1 keV energies show more variability in response to the solar wind changes, while the lower energy (<1 keV) ions are relatively stable. During the in-storm interval, O + ions show maximum flux enhancement and become further prominent during CME storms. O + ion (≥10 keV) fluxes show good correlation with − VswBz, and Sym-H index during CME-driven storms in the L ∼2.5–5.5. Apart from this, the average duration of persistence (〈Δt〉) for enhanced fluxes is higher for CIR-driven storm𝐴𝐴s with ⟨Δ𝐴𝐴𝑡𝑡⟩𝑂𝑂+ >⟨Δ𝐴𝐴𝑡𝑡⟩𝐻𝐻𝐻𝐻+ >⟨Δ𝑡𝑡⟩𝐻𝐻+ at E ≤ 50 keV in the L ∼2.5–5.5. Moreover, the observed value of 〈Δt〉i (where i is O +, H + or He +) increases with the increasing L. We discuss the plausible mechanisms to provide a comprehensive overview of L-values and energy sorted O +, He + and H + ion dynamics for two different categories of solar wind drivers.
Keywords: L-Value; CME; CIR Storms; Van Allen Probes